ANALYSIS OF THE FACTORS OF INFLUENCE IS ON MANAGEMENT OF ENTERPRISE HUMAN CAPITAL - HRECHYSHKINA, TETIANA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the theoretical approaches to the definition of human capital and theoretical approaches to human capital management. The process of identifying the abilities, knowledge and skills of individuals is one of the central tasks of human capital management. It is established that traditional management methods, including the processes of planning, hiring, evaluating, developing and motivating staff, aimed at its effective use and achieving the goals of the enterprise and employees, must meet modern trends in digital transformation. The article analyzes the influence of external (demographic situation, level of education, level of health care, cultural development) and internal factors (information development, personal investment in education) on the formation of human capital. The special influence of "artificial intelligence" on the formation of approaches to human capital management is revealed. There is an introduction of a new quality model of the current system of training and development of national culture, corporate culture, personal culture, in order to create a favorable economic climate. The control function should include determining the degree of efficiency of human capital use. It is determined that enterprises do not have a single system of indicators for assessing the quality of human capital, because it is impossible to give an objective assessment of the category of human capital. The individual is a rather complex central element of the economic population, so it is possible to analyze the deviation of the goals of the industry, enterprise, department, manager from the development strategy, goals, management. If raising the level of human capital helps to increase its capacity, it will undoubtedly affect the performance of delegated responsibilities and the effectiveness of the organization. Recommendations have been developed that will allow in the current conditions of human capital management to have a qualitative impact on increasing the competitiveness of enterprises, regardless of the size and volume of production.
Keywords: human capital; competitive advantages; human potential; personality culture; management tools